2014
DOI: 10.2478/prilozi-2014-0020
|View full text |Cite
|
Sign up to set email alerts
|

T-Scan III System Diagnostic Tool for Digital Occlusal Analysis in Orthodontics – a Modern Approach

Abstract: Introduction: This systematic literature review was performed to establish the mechanism, methodology, characteristics, clinical application and opportunities of the T-Scan III System as a diagnostic tool for digital occlusal analysis in different fields of dentistry, precisely in orthodontics. Methods: Searching of electronic databases, using MEDLINE and PubMed, hand searching of relevant key journals, and screening of reference lists of included studies with no language restriction was performed. Publication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 11 publications
1
22
0
5
Order By: Relevance
“…T-Scan (T-Scan III, Software version 8.0.1, Tekscan, Inc., Boston, MA, USA) is a digital occlusion analysis system that records and measures tooth contact, force, and timing in real-time using a thin, flexible, pressure-sensitive bite transducer embedded in a dental arch-shaped recording sensor 4, 10–12 (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…T-Scan (T-Scan III, Software version 8.0.1, Tekscan, Inc., Boston, MA, USA) is a digital occlusion analysis system that records and measures tooth contact, force, and timing in real-time using a thin, flexible, pressure-sensitive bite transducer embedded in a dental arch-shaped recording sensor 4, 10–12 (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…The proper occlusion in complete denture is the crucial factor to improve the success of the treatment. Using computerised occlusal analysis assists the dentist to detect occlusal force and occlusal distribution and allow the dentist to adjust the occlusion accurately 30‐34 . It is also used together with conventional articulating paper 26 …”
Section: Discussionmentioning
confidence: 99%
“…It was found that occlusal indicator is reliable to assist in occlusal adjustment 30,31 . T‐Scan ® (Tekscan, Inc) is a digital occlusal analysis system for recording and measuring tooth contact, force distribution and timing in real‐time using pressure‐sensitive bite transducer 32‐34 . The occlusal force distribution, occlusal interference and relative force of each interference can be determined from the occlusal recorded 32,33 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(9) This device is used in many clinical situations when occlusal adjustment is necessary as Complete dentures, fixed or removable partial dentures, Complete arch reconstruction by using implants, Complete arch reconstruction involving FPD, Natural tooth occlusal equilibration, Occlusal splints, Mandibular repositioning devices. (10) Sensitivity, reliability, reproducibility are the major advantages when T scan is used for the digital occlusal analysis (11,12) as it has the ability to record the very first contact of tooth, relative force and timing (13) The current version of T scan used recently is T scan III.…”
Section: Introductionmentioning
confidence: 99%